Public perceptions and behaviours related to the risk of infection with Aedes mosquito-borne diseases: a cross-sectional study in Southeastern France. Issue 6 (28th November 2012) - Raude, Jocelyn; Chinfatt, Kimberly; Huang, Peiching; Betansedi, Charles Olivier; Katumba, Kenneth; Vernazza, Nicole; Bley, Daniel
Abstract : Objectives: To explore public perceptions and behaviours related to the risk of flavivirus and alphavirus infection in Southeastern regions of France following the recent colonisation of the Asian tiger mosquito, Aedes albopictus, and the identification of four autochthonous cases of dengue and chikungunya fever in these regions. Design: Cross-sectional telephone survey using a proportional random digit dialling selection method. Setting: Interviews were conducted from 28 November 2011 to 29 January 2012 using a computer-assisted telephone interviewing system. Participants: 1506 French speaking adults aged 18 years or older residing in French Mediterranean regions. Results: Protective health behaviours were found to be performed less frequently among men (AOR=0.65, 95% CI 0.52% to 0.80%), residents with lower educational status (AOR=0.61, 95% CI 0.43% to 0.85% for respondents with primary school education; AOR=0.69, 95% CI 0.53% to 0.90% for those with some secondary school education), and those living in regions where the Aedes mosquito is objectively rare (AOR=0.60, 95% CI 0.36% to 0.98% for Aude; AOR=0.63, 95% CI 0.44% to 0.89% for Herault; AOR=0.56, 95% CI 0.34% to 0.93% for Eastern Pyrenees). Empirical results also suggest that behavioural responses to infection risk are greater shaped by the perceived exposure to Aedes, notably the perceived frequency of mosquito bites (AOR=2.07, 95% CI 1.84% to 2.32%) and visual identification of Aedes mosquitoes in one's immediate environment (AOR=1.98, 95% CI 1.45% to 2.71%) rather than by other common predictors of protective behaviours. Conclusions: These findings may help with the development of innovative instruments designed to make more visible and personal the threat of flavivirus and alphavirus infections induced by the presence of A albopictus in order to promote significant behavioural changes among populations at risk.